2019
DOI: 10.1111/febs.15110
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cα mediates recovery of renal and mitochondrial functions following acute injury

Abstract: Previously, we have shown that active protein kinase Ca (PKCa) promotes recovery of mitochondrial function after injury in vitro [Nowak G & Bakajsova D (2012) Am J Physiol Renal Physiol 303, F515-F526]. This study examined whether PKCa regulates recovery of mitochondrial and kidney functions after ischemia-induced acute injury (AKI) in vivo. Markers of kidney injury were increased after bilateral ischemia and returned to normal levels in wild-type (WT) mice. Maximum mitochondrial respiration and activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Plasma levels of creatinine were used as a marker of renal function. Blood was drawn while mice were euthanized, spun down and plasma was used to determine creatinine concentration using the Creatinine Reagent Set from Biotron Diagnostics (Hemet, CA, USA) and the manufacturer’s protocol, as reported previously [ 56 , 57 , 58 ]. Plasma creatinine levels were determined in all mice used in the four experimental groups described on page 3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasma levels of creatinine were used as a marker of renal function. Blood was drawn while mice were euthanized, spun down and plasma was used to determine creatinine concentration using the Creatinine Reagent Set from Biotron Diagnostics (Hemet, CA, USA) and the manufacturer’s protocol, as reported previously [ 56 , 57 , 58 ]. Plasma creatinine levels were determined in all mice used in the four experimental groups described on page 3.…”
Section: Methodsmentioning
confidence: 99%
“…; Ovation Pharmaceuticals, Deerfield, IL, USA) and all surgical procedures were performed under sterile conditions. Following a midline incision of the abdomen, kidneys were exposed and decapsulated, and both renal hila were clamped for 35 min with small vascular clamps to induce bilateral renal ischemia as described previously [55][56][57][58]. While renal arteries of both kidneys were clamped, mice were placed on a heating pad that maintained a temperature of 37 • C. During that time, approximately 0.5 mL sterile saline was applied intraperitoneally to prevent fluid loss and dehydration.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Their results demonstrated that to protect against AKI, SIRT5 modulates the peroxisomal and mitochondrial FAO balance in PTECs (Chiba et al, 2019). Nowak and Megyesi (2019) concluded that the activation and translocation of protein kinase Cα (PKCα) to mitochondria restores normal mitochondrial function and kidney physiology. They observed that PKCa modulates the expression levels of SIRT3 and SIRT5 which were involved in de/acetylation and de/ succinylation of mitochondrial proteins (Nowak & Megyesi, 2019).…”
Section: Sirtuin 3 As a Crucial Modulator Of Mitochondrial Dynamicsmentioning
confidence: 99%